La imagen fotográfica como promotora de la identidad cultural y turística de la ciudad de Loja, Ecuador - Gualan Auquilla, Claudio Javier (2024)
This research seeks to make the city of Loja visible and encourage exploration of sites that are important, but have not been publicized, even for the local population. For this, the attributes and attractions of the city of Loja were identified, disseminated as a tourist image of the city. To obtain the results of this research, observation was used as a tool to identify and analyze the images of the tourist guide that exists in the Department of Tourism in the Municipality of Loja. Through the analysis of four sites in which the image of the city of Loja is promoted, it was possible to collect the necessary information to discover if photography as a communicative instrument plays a fundamental role in making visible the culture, architecture and traditions of a city. Our research allowed us to show that there is a deficit of technical areas in terms of photography, since the majority of images were not captured by a professional but by amateurs who visited certain places. Likewise, we were able to verify that six places and the same images are repeated in the analyzed sites. We were also able to observe that no clear information is presented that accompanies the images and serves visitors to have specific information about the city. This led us to create a site that incorporates the information collected within the theoretical framework about the elements that make up the cultural identity of the city of Loja. Keywords: Photography; cultural identity; Tourism; cultural hall.